Reaksi Nilai Tukar terhadap Informasi Fundamental dan "Berita" (News): Negara-Negara Asia Pasifik 2003-2006 - Damayanti, Damayanti (Jurnal Ekonomi dan Pembangunan Indonesia, 2008)
This research analyses the link between economic fundamentals and news with exchange rates. We find that such economic news in Asia Pasific in the period 2003-2006. The exchange rate is shown to respond more strongly to news in last periods of large market uncertainty.